Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 4 - Proportions, Percents, and Solving Inequalities - Chapters 1-4 Cumulative Review Problem Set - Page 186: 13



Work Step by Step

Using the distributive property and combining like terms, the given expression simplifies to: $-3(x-1)+2(x+6)$ =$-3x+3+2x+12$ =$-3x+2x+3+12$ =$-x+15$ We substitute $x=-5$ in the expression and simplify: $-x+15$ =$-(-5)+15$ =$5+15$ =$20$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.